Personality Characteristics of University Athletes Based on Gender - Aldiansyah; Surdiniaty Ugelta; Unun Umaran (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aims to describe the personality characteristics of university athletes based on the Big Five Personality Traits model and to analyze differences between male and female athletes. This study is expected to provide theoretical contributions in strengthening the application of the Big Five model in the context of university sports in Indonesia, as well as providing practical contributions for coaches and educational institutions in designing psychological coaching strategies that are more adaptive, gender-sensitive, and evidence-based. A quantitative approach with a descriptive-comparative design was employed. The sample consisted of 200 university athletes from student sport units at Universitas Pendidikan Indonesia, including 100 male and 100 female athletes. Data were collected using the Big Five Inventory-10 (BFI-10) and analyzed through descriptive statistics and paired-sample t-tests. The results indicate that university athletes exhibit relatively high mean scores across all personality dimensions, with openness to experience showing the highest mean (M = 7.40; SD = 1.41). Inferential analysis revealed a significant overall difference in personality characteristics between male and female athletes (t = 7.264; p < 0.05). Significant differences were also found in extraversion (t = 3.637), neuroticism (t = 2.447), openness to experience (t = 3.250), agreeableness (t = 6.438), and conscientiousness (t = 4.501). This study concludes that personality characteristics of university athletes differ significantly by gender, highlighting the importance of considering gender differences in athlete development and training programs in higher education.